STATISTICAL SECURITY OF ECONOMIC MANAGEMENT - HRYTSUN, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Modern integrated economic statistics is a set of economic and statistical data that reflect a consistent and holistic picture of economic activity for political, commercial and other analytical purposes. In analyzing the historical aspect of the emergence and development of statistical practice, we have shown that its origin occurred around the time when the state emerged. There is information about the elementary recount (census) of population and land, which was conducted several millennia ago. With the formation of a centralized state and especially with its development, the scope of statistics has expanded significantly.It is established that the statistical support of effective development of enterprises of Ukraine in the scale of a particular industry can be realized according to official statistics, namely: statistical observations of the volume of sold industrial products and operating costs of sold products. It is emphasized that today the volume and structure of data presented on the official website of statistics of Ukraine, is considered insufficient for full information support of management processes of industrial enterprises.The approaches of scholars to the interpretation of the role of statistical methods of analysis for successful economic management are considered. The basic mathematical and statistical methods are listed and their short characteristic is given. It is established that the profitability indicator is chosen as a general indicator of efficiency and technological level of enterprises of the studied industries.Construction of the economic and mathematical model of profitability of products of separate industries made it possible to reveal production reserves to increase the efficiency of the enterprises. For mechanical engineering it means reducing the capital intensity of products used funds (depreciation). For metallurgy it means a reduction in material and labor intensity of products. For the production of chemical products it is reducing material consumption.When choosing statistical methods for studying socio-economic phenomena, it is necessary to take into account their interconnectedness and interdependence. Based on the results, the priority for the development of management decisions for the effective development of processing enterprises should be to increase the degree of processing of raw materials (to increase the technological level of production), increase productivity of fixed assets and increase final consumption.
Keywords: economics management; statistical research; dispersion method; profitability modeling